ANALISIS PENGARUH DIGITAL MARKETING TERHADAP BISNIS ONLINE DALAM PENGAMBILAN KEPUTUSAN STUDI KASUS PADA PEDAGANG ONLINE SHOP - Setiani, Revia; Yanti, Jumianis (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
This study aims to see the impact of digital marketing on the development of online shops, especially in relation to consumer purchasing decisions. In the midst of the advancement of the digital era, marketing methods are undergoing a transformation from traditional methods to more modern and technology-based approaches. Digital marketing has a strategic role in reaching consumers more widely, quickly, and effectively. This study was conducted with a quantitative approach by distributing surveys to consumers who actively use digital platforms. The results of the analysis show that digital marketing components such as social media, email marketing, search engine optimization (SEO), and digital advertising as well as ease of obtaining information, direct communication with sales have a significant influence on increasing purchasing decisions. This finding confirms that optimal use of digital marketing can increase the competitiveness of online businesses and strengthen relationships with consumers and can expand the reach of online shop businesses.